Self-assembled polymeric nanoparticles as new, smart contrast agents for cancer early detection using magnetic resonance imaging - Mouffouk, Fouzi (2016)
Early cancer detection is a major factor in the reduction of mortality and cancer management cost. Here we developed a smart and targeted micelle-based contrast agent for magnetic resonance imaging (MRI), able to turn on its imaging capability in the presence of acidic cancer tissues. This smart contrast agent consists of pH-sensitive polymeric micelles formed by self-assembly of a diblock copolymer (poly(ethyleneglycol-b-trimethylsilyl methacrylate)), loaded with a gadolinium hydrophobic complex ((t)BuBipyGd) and exploits the acidic pH in cancer tissues. In vitro MRI experiments showed that (t)BuBipyGd-loaded micelles were pH-sensitive, as they turned on their imaging capability only in an acidic microenvironment. The micelle-targeting ability toward cancer cells was enhanced by conjugation with an antibody against the MUC1 protein. The ability of our antibody-decorated micelles to be switched on in acidic microenvironments and to target cancer cells expressing specific antigens, together with its high Gd(III) content and its small size (35-40 nm) reveals their potential use for early cancer detection by MRI.